Regulation of synaptic transmission by BDNF : effects on NMDA receptor-mediated mEPSCs - Luca, Pasqualino De (2016)
Brain derived neurotrophic factor (BDNF) plays an important role in long-term synaptic potentiation (LTP) in the hippocampus, partially due to the upregulation of translation activity. However, the molecular mechanisms are not fully understood. In this work we investigated the effect of BDNF of the surface expression of N-methyl-D-aspartate receptors, which play a key role in synaptic plasticity. Stimulation of cultured hippocampal neurons with BDNF induced the synaptic accumulation of GluN2B-containing NMDAR, as determined by immunocytochemistry with an antibody against the N-terminal region of the receptor subunit and by colocalization with pre- and post-synaptic markers, the vesicular glutamate transporter type 1 (vGlut1) and postsynaptic density protein 95 (PSD-95), respectively. The effect of BDNF on the amplitude and frequency of NMDAR mediated miniature excitatory postsynaptic currents (mEPSCs) was also evaluated under the same conditions by voltage-clamp recordings. Incubation of cultured hippocampal neurons with BDNF upregulated the amplitude of NMDA receptor-mediated mEPSC, but did not change the rise and decay time. The enhancement in the amplitude of the currents was abrogated by the GluN2B competitive antagonist Conantokin G, in agreement with the results obtained in the immunocytochemistry experiments. Antibody-feeding experiments showed no significant alteration in the rate of internalization of GluN2B-containing NMDA receptors following incubation of the neurotrophin, suggesting that a different mechanism is involved. The BDNF-evoked upregulation of GluN2B surface expression, as well as the increase in the amplitude of mEPSC, were abrogated by the protein synthesis inhibitor cycloheximide, suggesting a role for local translation activity. Based on unpublished observations from the laboratory showing a key role for the hnRNP K (heterogeneous nuclear ribonucleoprotein K) RNA binding protein in the regulation of protein synthesis by BDNF, we characterized the role of this protein in the neurotrophin-induced upregulation of NMDA receptor mediated mEPSC. Transfection of hippocampal neurons with an shRNA against hnRNP K suppressed the effects of BDNF on the amplitude of mEPSC. Considering the available evidence showing that BDNF upregulates Pyk2 protein levels in hippocampal neurons by a mechanism dependent on hnRNP K, we hypothesized that de novo synthesis of the kinase could play a role in the regulation of the synaptic expression of GluN2B-containing NMDA receptors by BDNF. Transfection of hippocampal neurons with an shRNA specific for Pyk2 abrogated the BDNF-evoked increase in the amplitude of the NMDA receptor-mediated mEPSC, showing a role for the kinase as a mediator of the TrkB-BDNF signaling to regulate the activity of NMDA receptors. BDNF also increased the frequency of NMDA receptor mediated mEPSC in cultured hippocampal neurons, by a mechanism sensitive to cycloheximide and possibly dependent on the presence of hnRNP K. This shows a presynaptic response to BDNF in glutamatergic synapses, which requires protein synthesis. Together, the results show a novel effect of BDNF in the regulation of the synaptic expression of NMDA receptors that is mediated by the RNA binding protein hnRNP K, as well as by the Pyk2 tyrosine kinase. These alterations in the surface expression of NMDA receptors may play an important role in LTP in the hippocampus.